Association between alcohol consumption and overweight among university students in Latin America - Parra Soto, Solange Liliana.; Araya, Carolina; Morales, Gladys; Araneda Flores, Jacqueline.; Landaeta Diaz, Leslie Lorena.; Murillo, Ana Gabriela; Gómez, Georgina; Ríos Castillo, Israel.; Carpio Arias, Tannia Valeria.; Cavagnari, Brian Martín; Nava González, Edna J.; Bejarano Roncancio, Jhon Jairo.; et al. (Sociedad Chilena de Nutrición Bromatología y Toxicológica, 2023)
Introduction: Overweight and obesity are public health problems worldwide. Alcoholic beverages could increase total energy intake causing an increase in body weight. However, few authors have pointed out the association between this habit and excess weight in this population. The objective of this study was to determine the association between alcohol consumption and excess weight in university students from 10 Latin American countries during the COVID-19 pandemic. Methodology: A cross-sectional and multicenter study was carried out with 4,539 university students enrolled in ten Latin American countries. To assess alcohol consumption, the question Do you consume alcoholic beverages? (1 portion 1 glass of 200 ml). Body mass index (BMI) kg/m2 was determined from self-reported weight and height. To determine if excess weight was associated with alcohol consumption, a logistic regression analysis was used, adjusted for age, sex, year of study, socioeconomic level, physical activity, and smoking. Results: Among students with normal nutritional status, 59.6% did not consume alcohol, while among those with a BMI ≥25 kg/m2 it was 55.1%. Students who consumed 2 or more servings of alcohol per day had a 2.18 times greater risk of being overweight (OR: 2.18 [95% CI: 1.26 to 3.77]), compared with those who did not consume alcohol. Conclusion: It was observed that those students who consumed more alcohol were more likely to be overweight.
Keywords: Body Mass Index; Overweight; University Students; Alcohol; Obesidad